2018
DOI: 10.1038/nrd.2018.180
|View full text |Cite
|
Sign up to set email alerts
|

GPCR drug discovery: integrating solution NMR data with crystal and cryo-EM structures

Abstract: The 826 G protein-coupled receptors (GPCRs) in the human proteome regulate key physiological processes, and thus have long been attractive as drug targets. With crystal structure determinations of more than 50 different human GPCRs during the last decade, an initial platform for structure-based rational design has been established for drugs that target GPCRs, which is currently being augmented with cryo-EM structures of higher-order GPCR complexes. Nuclear magnetic resonance (NMR) spectroscopy in solution is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
181
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(189 citation statements)
references
References 274 publications
1
181
0
7
Order By: Relevance
“…In addition to this static picture, NMR spectroscopy has demonstrated that these receptors are highly dynamic proteins, which populate multiple states that are in equilibrium with each other 12 . NMR has determined exchange kinetics and populations for some of these interconverting states 13,14 . Investigations of several class A receptors have revealed that their energy landscapes are unique with the differences relating to their individual signalling properties [15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…In addition to this static picture, NMR spectroscopy has demonstrated that these receptors are highly dynamic proteins, which populate multiple states that are in equilibrium with each other 12 . NMR has determined exchange kinetics and populations for some of these interconverting states 13,14 . Investigations of several class A receptors have revealed that their energy landscapes are unique with the differences relating to their individual signalling properties [15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…Atomic-resolution structures are now available for more than 50 different GPCRs and over 250 of their complexes with different ligands (Shimada, Ueda et al , 2018). Crystal structures of C5aR in complex with NDT9513727, PMX53 and avacopan have recently been reported (Liu, Kim et al , 2018; Robertson, Rappas et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As transcriptional regulations by preexisting conformational equilibria have been suggested to act in bacterial repressors as well as eukaryotic nuclear receptors (27,28), the conformational selection mechanisms would be shared widely among the ligand-inducible types of transcriptional regulators. The conformational equilibrium also allows various levels of responses in different biological systems such as G protein-coupled receptors (GPCRs), ion channels, kinases, and molecular chaperons (29)(30)(31)(32)(33)(34)(35)(36)(37)(38), which might be a fundamental mechanism shared by biological systems that require rapid responses to exert their functions.…”
Section: Discussionmentioning
confidence: 99%